Coal-based activated carbon and preparation method thereof

By using activators such as nitrate, carbonate and chloride in the preparation process of coal-based activated carbon, combined with carbonization and activation treatment, the problems of long activation time, high calcination loss and low yield of coal-based activated carbon are solved, and the effect of increasing activation rate, reducing calcination loss rate and improving yield is achieved.

CN119637870APending Publication Date: 2025-03-18CHINA ENERGY GRP NINGXIA COAL IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411675339.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, there are problems such as long time, high burnout and low yield in the preparation process of coal-quality activated carbon.

Method used

By adding activators (nitrates, carbonates and chlorides), coal tar and water to the raw coal powder, carbonization and activation treatment, the activation efficiency, yield and performance of coal-quality activated carbon are improved.

Benefits of technology

The activation rate of coal-quality activated carbon is improved, the firing loss rate of raw materials is reduced, the activation yield is improved, and the pore structure and adsorption performance are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146863010000081
    Figure BDA0005146863010000081
Patent Text Reader

Abstract

The invention provides coal-based activated carbon and a preparation method thereof. The preparation method of the coal-based activated carbon comprises the following steps: S1, mixing raw material pulverized coal, an activating agent, coal tar and water, and performing extrusion molding to obtain a molded material; the weight ratio of the raw material pulverized coal to the activating agent to the coal tar is 1: (0.4-1.0%): (0.32-0.42), and the activating agent comprises nitrate, carbonate and chloride; s2, under the inert gas atmosphere, the formed material is subjected to carbonization treatment, and a carbonized material is obtained; the carbonization treatment temperature is 650 DEG C to 800 DEG C; s3, activating the carbonized material to obtain coal-based activated carbon; the activation treatment temperature is 900-960 DEG C, and the activation gas is water vapor, so that the problems of long time required by the activation process of the activated carbon, high carbon ignition loss and low yield in the preparation process of the coal-based activated carbon in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon material preparation, and in particular to coal-based activated carbon and a preparation method thereof. Background Art

[0002] Activated carbon is widely used in air purification, wastewater purification, flue gas desulfurization and denitrification, flue gas demercurization and food processing due to its good adsorption and regeneration properties. Activated carbon can be divided into wood activated carbon and coal activated carbon according to the raw materials.

[0003] In the preparation process of coal-based activated carbon, raw coal is one of the main factors that determine its pore structure and adsorption performance. Lignite, bituminous coal, and anthracite can all be used as raw materials for coal-based activated carbon. Their properties are different, and the activated carbon produced has different pore size distributions and adsorption characteristics. Lignite has the strongest reactivity, and anthracite has the weakest reactivity. Generally speaking, the type of coal used to produce high-quality activated carbon must have both low ash content and high activity, but due to coal quality reasons, it is difficult to have both. For example, compared with bituminous coal and lignite, anthracite has lower chemical reactivity. The activation process for preparing activated carbon with the same technical indicators takes a long time, the loss on ignition is high, and the yield is low. Therefore, it is of great significance to develop a preparation process for coal-based activated carbon, reduce the activation time and loss on ignition of coal-based activated carbon, and increase the yield of coal-based activated carbon. Summary of the invention

[0004] The main purpose of the present invention is to provide a coal-based activated carbon and a preparation method thereof, so as to solve the problems of long time required for the activated carbon activation process, high ignition loss and low yield in the preparation process of coal-based activated carbon in the prior art.

[0005] In order to achieve the above object, the present invention provides a method for preparing coal-based activated carbon, comprising the following steps:

[0006] Step S1, mixing raw coal powder, activator, coal tar and water and then extruding to obtain a molding material; the weight ratio of the raw coal powder, activator and coal tar is 1: (0.4%-1.0%): (0.32-0.42), and the activator includes nitrate, carbonate and chloride;

[0007] Step S2, in an inert gas atmosphere, carbonizing the molding material to obtain a carbonized material; the temperature of the carbonization treatment is 650° C. to 800° C.;

[0008] Step S3, activating the carbonized material to obtain coal-based activated carbon; the activation temperature is 900° C. to 960° C., and the activation gas is water vapor.

[0009] Furthermore, the weight ratio of nitrate, carbonate and chloride is (1-2):(1-2):(1-2).

[0010] Further, the nitrate is selected from Zn(NO 3 ) 2 、Ca(NO 3 ) 2 、NaNO 3 One or more of .

[0011] Further, the carbonate is selected from Na 2 CO 3 , K 2 CO 3 One or a mixture of two in any proportion.

[0012] Further, the chloride is selected from ZnCl 2 MgCl 2 , CaCl 2 One or more of .

[0013] Furthermore, the particle size of the raw coal powder is less than 0.1 mm.

[0014] Furthermore, the raw coal powder is anthracite coal powder.

[0015] Preferably, the volatile matter content of the anthracite pulverized coal is 4.0% to 8.0%.

[0016] Furthermore, in step S1, the raw coal powder, activator, coal tar and water are first stirred and mixed in a kneader at 55-65° C. to obtain a mixture, and then the mixture is extruded by an extrusion molding device to obtain a molding material.

[0017] Preferably, the raw coal powder and the activator are first stirred and mixed in a kneader at 55-65° C., and then coal tar and water are added and stirred and mixed in the kneader to obtain a mixture.

[0018] Preferably, the molding material is in a strip-shaped structure.

[0019] Preferably, the weight ratio of raw coal powder to water is (10-15):1.

[0020] Furthermore, in step S2, the heating rate of the carbonization treatment is 5°C / min to 15°C / min.

[0021] Preferably, in step S2, the molding material is dried before the carbonization treatment.

[0022] More preferably, the drying process is performed by natural air drying.

[0023] More preferably, in step S2, under an inert gas atmosphere, the temperature in the furnace is first raised to 250°C to 300°C, and then the dried molding material is placed in the furnace for carbonization treatment.

[0024] Preferably, the carbonization treatment time is 10 min to 30 min.

[0025] Furthermore, in step S3, the heating rate of the activation treatment is 5°C / min to 15°C / min.

[0026] Preferably, the amount of activated gas introduced is calculated based on a flow rate of 10 ml / min to 30 ml / min of activated gas per kilogram of raw coal powder.

[0027] Preferably, the activation time is 20 min to 100 min.

[0028] According to another aspect of the present invention, there is provided coal-based activated carbon prepared according to the above method for preparing coal-based activated carbon.

[0029] The technical scheme of the present invention is applied, by adding activators (nitrates, carbonates and chlorides), coal tar and water to raw coal powder, using coal tar as a binder, extruding the raw coal powder to obtain a molding material, and then carbonizing and activating the material, the activation efficiency, yield and performance of coal-based activated carbon can be improved. During the carbonization process, nitrates are decomposed by heat to produce oxygen and alkaline oxides, and oxygen can oxidize the raw coal powder, which is conducive to forming a rich pore structure in a short time. At the same time, nitrates can react with oxygen-containing functional groups in the raw coal powder to promote the dehydrogenation polymerization of the raw coal to form amorphous carbon, reduce the raw material loss rate, and in the activation process, the large number of pores formed enable water vapor to react evenly and quickly with the inside and surface of the carbonized product to activate, improve the activation rate, reduce carbon loss, and improve the activation yield. In addition, the alkaline oxides produced by the decomposition of nitrates can react with the insoluble silicates in the coal ash to form soluble silicates, so as to achieve the purpose of improving the activation speed. The formed soluble silicates can be removed by subsequent hot water washing and dilute hydrochloric acid washing to reduce the ash content of the product. During the activation process, as the temperature rises, carbonates are thermally decomposed to generate carbon dioxide and metal oxides. The carbon dioxide gas will expand and generate pressure inside the carbonized material, causing the microporous structure of the activated carbon to collapse or the pore walls to burn, tending to produce more mesopores and macropores, thereby increasing the activation rate. In addition, the metal oxides generated by the decomposition of carbonates are alkaline and can also react with sparingly soluble silicates in the coal ash to form soluble silicates, which can increase the activation rate and product ash content. During the carbonization process, chlorides can activate the raw coal to form active sites, promote the dehydrogenation polymerization of the raw coal to form amorphous carbon, reduce the raw material burnout rate, and facilitate the formation of micropores for subsequent further activation to form larger mesopores, increase the specific surface area and porosity of coal-based activated carbon, and improve its adsorption performance.

[0030] The method of the invention can improve the activation rate of coal-based activated carbon, reduce the burning rate of raw materials, and improve the activation yield. DETAILED DESCRIPTION

[0031] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0032] As described in the background technology, the prior art has the problems that the activated carbon activation process takes a long time, the ignition loss is high and the yield is low during the preparation of coal-based activated carbon. In order to solve the above problems, the present invention provides a method for preparing coal-based activated carbon, comprising the following steps:

[0033] Step S1, mixing raw coal powder, activator, coal tar and water and then extruding to obtain a molding material; the weight ratio of the raw coal powder, activator and coal tar is 1: (0.4%-1.0%): (0.32-0.42), and the activator includes nitrate, carbonate and chloride;

[0034] Step S2, in an inert gas atmosphere, carbonizing the molding material to obtain a carbonized material; the temperature of the carbonization treatment is 600° C. to 800° C.;

[0035] Step S3, activating the carbonized material to obtain coal-based activated carbon; the activation temperature is 900° C. to 960° C., and the activation gas is water vapor.

[0036] According to the preparation method of coal-based activated carbon of the present invention, coal tar is used as a binder, raw coal powder is extruded and molded to obtain a molded material, and an activator (nitrate, carbonate and chloride), coal tar and water are added to the raw coal powder, and then carbonization and activation treatment are performed, so as to improve the activation efficiency, yield and performance of coal-based activated carbon. During the carbonization process, nitrate is decomposed by heat to produce oxygen and alkaline oxides, and oxygen can oxidize the raw coal powder, which is conducive to forming a rich pore structure in a short time. At the same time, nitrate can react with oxygen-containing functional groups in the raw coal powder to promote the dehydrogenation polymerization of the raw coal to form amorphous carbon, reduce the raw material burn-off rate, and during the activation process, a large number of pores are formed to enable water vapor to evenly and quickly react with the inside and surface of the carbonized product to activate, thereby increasing the activation rate, reducing the carbon burn-off rate, and increasing the activation yield. In addition, the alkaline oxides produced by the decomposition of nitrates can react with the sparingly soluble silicates in the coal ash to form soluble silicates, thereby increasing the activation rate. The soluble silicates can be removed by subsequent hot water washing and dilute hydrochloric acid washing to reduce the ash content of the product. During the activation process, as the temperature rises, carbonates are thermally decomposed to form carbon dioxide and metal oxides. The carbon dioxide gas will expand and generate pressure inside the carbonized material, causing the microporous structure of the activated carbon to collapse or the pore wall to ablate, tending to produce more mesopores and macropores, thereby increasing the activation rate. In addition, the metal oxides produced by the decomposition of carbonates are alkaline and can also react with the sparingly soluble silicates in the coal ash to form soluble silicates, thereby increasing the activation rate and the ash content of the product. During the carbonization process, chlorides can activate the raw coal to form active sites, promote the dehydrogenation polymerization of the raw coal to form amorphous carbon, reduce the raw material burnout rate, and facilitate the formation of micropores so that further activation can form larger mesopores, increase the specific surface area and porosity of coal-based activated carbon, and improve its adsorption performance. The method of the invention can improve the activation rate of coal-based activated carbon, reduce the burning rate of raw materials, and improve the activation yield.

[0037] In some embodiments, the weight ratio of nitrate, carbonate and chloride is (1-2): (1-2): (1-2). The oxidation promotion effect of nitrate, the pore optimization effect of carbonate and the dehydrogenation polymerization effect of chloride cooperate with each other to improve the activation efficiency and porosity of activated carbon and optimize the pore structure, thereby improving the adsorption performance, activation efficiency and yield of activated carbon.

[0038] In some embodiments, the nitrate is selected from Zn(NO 3 ) 2 、Ca(NO 3 ) 2 、NaNO 3 The three nitrates mentioned above are easily and fully decomposed at the above carbonization temperature to provide oxygen, promote the oxidation of raw coal powder, and help form a more stable carbon structure and more pores.

[0039] In some embodiments, the carbonate is selected from Na 2 CO 3 , K 2 CO 3 The carbonates mentioned above are easily decomposed at the activation temperature to produce carbon dioxide gas, which is helpful for the formation of pores, and the generated metal oxides (such as Na 2 O or K 2 O) can react with the silicate acidic components in the coal ash to form soluble sodium silicate and potassium silicate, which is beneficial to improve the activation efficiency and optimize the pore structure.

[0040] In some embodiments, the chloride is selected from ZnCl 2 MgCl 2 , CaCl 2 The above chlorides are beneficial to obtain higher dehydrogenation polymerization efficiency and to improve activation efficiency and porosity of coal-based activated carbon.

[0041] In some embodiments, the particle size of the raw coal powder is less than 0.1 mm, which helps to improve the mixing uniformity so that the activator and the raw coal powder can fully contact and react.

[0042] In some embodiments, the raw coal powder is anthracite coal powder, and the content and properties of volatile matter have an important influence on the calorific value of coal, combustion characteristics, and carbonization reaction and activation reaction in the process of preparing activated carbon. For example, high-volatile coal tends to form more gas when heated, which is conducive to the formation of pores in the carbonization and activation stages, but at the same time it will increase the instability of the raw coal powder during the heating process, increase the loss on ignition, and reduce the yield of activated carbon. Anthracite has a lower ash content and a higher carbon content, which is conducive to the formation of high-purity and high-yield coal-based activated carbon. At the same time, the activation efficiency and porosity are improved by activation with an activator, so as to obtain coal-based activated carbon with high activation rate, low raw material loss on ignition rate, high yield and high quality. Preferably, the volatile matter content in the raw coal powder is 4.0% to 8.0%, and the volatile matter content in the raw coal powder is within the above range, which is conducive to obtaining coal-based activated carbon with high porosity, stable carbon structure and high yield.

[0043] In some embodiments, in step S1, the raw coal powder, activator, coal tar and water are first stirred and mixed in a kneader at 55°C to 65°C to obtain a mixture, and then the mixture is extruded and molded by an extrusion molding device to obtain a molding material. The raw materials and the activator are fully mixed by stirring and molding to improve the subsequent carbonization and activation efficiency; preferably, the raw coal powder and the activator are first stirred and mixed in a kneader at 55°C to 65°C, and then coal tar and water are added to the kneader and stirred and mixed to obtain a mixture. The raw coal powder and the activator are first mixed at 55°C to 65°C, and then coal tar and water are added to the kneader to disperse the coal tar and the raw coal powder to improve the mixing efficiency and uniformity; preferably, the molding material is a strip structure. The use of strip molding material can increase the heating area in the subsequent carbonization and activation process and promote the uniformity of the reaction; preferably, the weight ratio of raw coal powder to water is (10-15):1, which is conducive to molding and better maintaining the shape of the molding material.

[0044] In some embodiments, in step S2, the heating rate of the carbonization treatment is 5°C / min to 15°C / min. The above-mentioned heating rate of the carbonization treatment is beneficial to reducing the destruction of the carbon structure caused by the excessive internal reaction of the raw materials during the carbonization process, thereby improving the stability of the carbonization process and the quality of the carbonized material; preferably, in step S2, the molding material is dried before the carbonization treatment, and the drying treatment helps to remove moisture from the raw materials, reduce the influence of steam during the carbonization process, and improve the subsequent carbonization efficiency and the yield of the carbonized material; more preferably, the drying treatment is carried out by natural air drying, and the operation is carried out in an order-by-order manner to save energy consumption; more preferably, in step S2, under an inert gas atmosphere, the temperature in the furnace is first heated to 250°C to 350°C, and then the dried molding material is placed in the furnace for carbonization treatment, first heated to 250°C to 350°C, and then the molding material is placed in the furnace for direct high-temperature dehydration, decomposition, polymerization, etc., which can better maintain the shape of the molding material to prevent the coal strips from softening into irregular structures during the slow heating process; preferably, the carbonization treatment time is 10min to 30min.

[0045] In some embodiments, in step S3, the heating rate of the activation treatment is 5°C / min to 15°C / min. The above-mentioned heating rate of the activation treatment is beneficial to reducing the destruction of the carbon structure caused by excessive internal reaction of the raw materials during the activation process, thereby improving the stability of the carbonization process and the quality of the carbonized material; the preferred amount of activation gas introduced is calculated at an activation gas flow rate of 10 to 30 ml / min per kilogram of raw coal powder, which is beneficial to forming a high porosity and uniform pore structure in the coal-based activated carbon, thereby improving the adsorption performance of the activated carbon; the preferred activation time is 20 min to 100 min.

[0046] In some embodiments, the carbonization treatment and the activation treatment are both carried out in a carbon activation integrated furnace. The carbon activation integrated furnace is a special equipment for the production of activated carbon, which combines the two key steps of carbonization and activation, and can complete the carbonization of raw materials and subsequent activation treatment in one furnace, thereby improving production efficiency and energy utilization efficiency.

[0047] According to another aspect of the present invention, there is provided coal-based activated carbon prepared according to the above method for preparing coal-based activated carbon.

[0048] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0049] Example 1

[0050] A method for preparing coal-based activated carbon comprises the following steps:

[0051] Step 1, grinding anthracite with a volatile content of 8% in a ball mill, and then sieving through a 200-mesh (0.074 mm) sieve to obtain anthracite pulverized coal;

[0052] Step 2: at 60°C, 5000g of anthracite coal powder and an activator are stirred in a kneader for 10 minutes, coal tar and water are added and stirred for 10 minutes to obtain a mixture, and then the mixture is extruded into a cylindrical coal strip with a diameter of 2mm by an extrusion molding device; wherein the weight ratio of anthracite coal powder to activator is 1:0.6%, the weight ratio of anthracite coal powder to coal tar is 1:0.34, and the activator is NaNO 3 , k 2 CO 3 and CaCl 2 The weight ratio of anthracite pulverized coal to water is 12:1.

[0053] Step 3: air-dry the coal strips naturally, then introduce nitrogen into the carbon activation integrated furnace and heat the carbon activation integrated furnace to 300°C, then place the air-dried coal strips in the carbon activation integrated furnace, heat the temperature to 750°C at a heating rate of 10°C / min, and keep the temperature for 20 minutes;

[0054] Step 4, after heating to 940°C at a heating rate of 10°C / min, stop introducing nitrogen and introduce water vapor at a flow rate of 30mL / min for activation treatment, keep warm for 30min, cool and discharge to obtain coal-based activated carbon.

[0055] Example 2

[0056] A method for preparing coal-based activated carbon comprises the following steps:

[0057] Step 1, grinding anthracite with a volatile content of 8% in a ball mill, and then sieving through a 200-mesh (0.074 mm) sieve to obtain anthracite pulverized coal;

[0058] Step 2: at 60°C, 5000g of anthracite powder and an activator are stirred in a kneader for 10 minutes, coal tar and water are added and stirred for 10 minutes to obtain a mixture, and then the mixture is extruded into a cylindrical coal strip with a diameter of 2mm by an extrusion molding device; wherein the weight ratio of anthracite powder to activator is 1:0.4%, the weight ratio of anthracite powder to coal tar is 1:0.32, and the activator is Ca(NO 3 ) 2 、Na 2 CO 3 and MgCl 2 The weight ratio of anthracite pulverized coal to water is 12:1.

[0059] Step 3, air-dry the coal strips naturally, introduce nitrogen into the carbon activation integrated furnace and heat the carbon activation integrated furnace to 300°C, place the air-dried coal strips in the carbon activation integrated furnace, heat the temperature to 600°C at a heating rate of 10°C / min, keep the temperature for 20 minutes, cool and discharge to obtain carbonized material;

[0060] Step 4, heat the integrated carbon activation furnace to 600°C, place the carbonized material in the integrated carbon activation furnace, heat it to 940°C at a heating rate of 10°C / min, introduce water vapor at a flow rate of 30mL / min for activation treatment, keep warm for 40 minutes, cool and discharge the material to obtain coal-based activated carbon.

[0061] Example 3

[0062] A method for preparing coal-based activated carbon comprises the following steps:

[0063] Step 1, grinding the raw material anthracite with a volatile content of 8% by a ball mill, and then sieving through a 200-mesh (0.074 mm) sieve to obtain anthracite pulverized coal;

[0064] Step 2: at 60°C, 5000g of anthracite coal powder and an activator are stirred in a kneader for 10 minutes, coal tar and water are added and stirred for 10 minutes to obtain a mixture, and then the mixture is extruded into a cylindrical coal strip with a diameter of 2mm by an extrusion molding device; wherein the weight ratio of anthracite coal powder to activator is 1:1%, the weight ratio of anthracite coal powder to coal tar is 1:0.42, and the activator is MgCl 2 , k 2 CO 3 and ZnCl 2The weight ratio of anthracite pulverized coal to water is 12:1.

[0065] Step 3, air-dry the coal strips naturally, introduce nitrogen into the carbon activation integrated furnace and heat the carbon activation integrated furnace to 300°C, place the air-dried coal strips in the carbon activation integrated furnace, heat the temperature to 800°C at a heating rate of 10°C / min, keep the temperature for 20 minutes, cool and discharge to obtain carbonized material;

[0066] Step 4, heat the integrated carbon activation furnace to 600°C, place the carbonized material in the integrated carbon activation furnace, heat it to 940°C at a heating rate of 10°C / min, introduce water vapor at a flow rate of 30mL / min for activation treatment, keep warm for 100min, cool and discharge the material to obtain coal-based activated carbon.

[0067] Example 4

[0068] The only difference between it and Example 1 is that the activator is NaNO 3 , k 2 CO 3 and CaCl 2 The mixture is obtained by mixing in a weight ratio of 3:1:1.

[0069] Example 5

[0070] The only difference between it and Example 1 is that the activator is NaNO 3 , k 2 CO 3 and CaCl 2 Mix them in a weight ratio of 1:3:1.

[0071] Example 6

[0072] The only difference between it and Example 1 is that the activator is NaNO 3 , k 2 CO 3 and CaCl 2 The mixture is obtained by mixing in a weight ratio of 1:1:3.

[0073] Comparative Example 1

[0074] The only difference between it and Example 1 is that no Zn(NO 3 ) 2 .

[0075] Comparative Example 2

[0076] The only difference between it and Example 1 is that no Zn(NO 3 ) 2 , and the activation time is 68min.

[0077] Comparative Example 3

[0078] The only difference between it and Example 1 is that no Na 2 CO 3 .

[0079] Comparative Example 4

[0080] The only difference between it and Example 1 is that no Na 2 CO 3 , and the activation time is 65min.

[0081] Comparative Example 5

[0082] The only difference between it and Example 1 is that no ZnCl is added. 2 .

[0083] Comparative Example 6

[0084] The only difference between it and Example 1 is that no ZnCl is added. 2 , and the activation time is 70min.

[0085] (1) The iodine adsorption value of coal-based activated carbon was determined according to GB / T7702.7-2008.

[0086] (2) The carbon tetrachloride adsorption rate of coal-based activated carbon was measured according to GB / T7702.13-2008.

[0087] (3) The wear resistance of coal-based activated carbon was measured according to GB / T7702.3-2008.

[0088] (4) The methylene blue adsorption value of coal-based activated carbon was determined according to GB / T7702.6-2008.

[0089] The yield, iodine value, carbon tetrachloride adsorption value and methylene blue value of the coal-based activated carbon prepared in Examples 1-6 and Comparative Examples 1-6 are shown in Table 1.

[0090] Table 1

[0091]

[0092] It can be seen from Table 1 that the coal-based activated carbon prepared in Examples 1-6 has high yield, high product iodine value and high carbon tetrachloride adsorption value, the carbon loss on ignition during the preparation process of the coal-based activated carbon is low, and the prepared coal-based activated carbon has rich pore structure and high mechanical strength.

[0093] The iodine value reflects the specific surface area and adsorption performance of the micropores of activated carbon by measuring its ability to adsorb iodine. Generally, the higher the iodine value of activated carbon, the more developed its micropores are, and the better the adsorption effect is on small molecules, such as organic pollutants, odor molecules, etc. The carbon tetrachloride adsorption value can reflect the mesoporous structure of activated carbon and its adsorption capacity for non-polar gases. The methylene blue value reflects the mesoporous and macroporous structure of activated carbon, as well as the adsorption efficiency of macromolecular organic compounds. Compared with Comparative Example 1 in which no nitrate activator is added, the iodine value, carbon tetrachloride value, and methylene blue value of the coal-based activated carbon prepared in Example 1 are significantly improved. The addition of nitrate activator is beneficial to improving the yield and activation rate of coal-based activated carbon. Under the same activation time, a rich pore structure is obtained, which significantly improves the amount of micropores, mesopores, and macropores.

[0094] Compared with Comparative Example 3 in which no carbonate activator was added, the carbon tetrachloride value and methylene blue value of the coal-based activated carbon prepared in Example 1 were significantly improved. The addition of the carbonate activator was beneficial to the generation of mesopores and macropores during the activation process. At the same activation time, it was beneficial to obtain coal-based activated carbon with more mesopores and macropores.

[0095] Compared with the comparative example 5 in which no chloride is added, the iodine value, carbon tetrachloride adsorption value and methylene blue value of the coal-based activated carbon prepared in Example 1 are significantly improved, especially the carbon tetrachloride adsorption value is significantly improved. The addition of chloride activator is beneficial to the generation of mesopores during activation. Under the same activation time, it is beneficial to obtain coal-based activated carbon with a more mesoporous structure.

[0096] By comparing Comparative Example 1, Comparative Example 2 with Example 1, Comparative Example 3, Comparative Example 4 with Example 1, and Comparative Example 5, Comparative Example 6 with Example 1, it can be seen that Comparative Example 2 without adding a nitrate activator, Comparative Example 4 without adding a carbonate, and Comparative Example 6 without adding a chloride, by more than doubling the activation time, although the iodine value, carbon tetrachloride value, and methylene blue value of the coal-based activated carbon can be improved to a certain extent, each value is still lower than that of Example 1, and the corresponding yield is also significantly reduced.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing coal-based activated carbon, characterized in that: The steps include: Step S1, mixing raw coal powder, an activator, coal tar and water and extruding to obtain a molding material; the weight ratio of the raw coal powder, the activator and the coal tar is 1: (0.4%-1.0%): (0.32-0.42), and the activator includes nitrate, carbonate and chloride; Step S2, in an inert gas atmosphere, carbonizing the molding material to obtain a carbonized material; the temperature of the carbonization treatment is 650° C. to 800° C.; Step S3, performing activation treatment on the carbonized material to obtain coal-based activated carbon; the activation treatment temperature is 900° C. to 960° C., and the activation gas is water vapor.

2. The method for preparing coal-based activated carbon according to claim 1, characterized in that: The weight ratio of the nitrate, carbonate and chloride is (1-3): (1-3): (1-2).

3. The method for preparing coal-based activated carbon according to claim 1, characterized in that: The nitrate is selected from one or more of Zn(NO3)2, Ca(NO3)2, and NaNO3.

4. The method for preparing coal-based activated carbon according to claim 1, characterized in that: The carbonate is selected from Na2CO3, K2CO3 or a mixture of the two in any proportion.

5. The method for preparing coal-based activated carbon according to claim 1, characterized in that: The chloride is selected from one or more of ZnCl2, MgCl2, and CaCl2.

6. The method for preparing coal-based activated carbon according to any one of claims 1 to 5, characterized in that: The particle size of the raw coal powder is less than 0.1 mm; and / or, The raw coal powder is anthracite coal powder; Preferably, the volatile matter content of the anthracite pulverized coal is 4.0% to 8.0%.

7. The method for preparing coal-based activated carbon according to any one of claims 1 to 5, characterized in that: In step S1, the raw coal powder, the activator, the coal tar and the water are first stirred and mixed in a kneader at 55-65° C. to obtain a mixture, and then the mixture is extruded by an extrusion molding device to obtain the molding material; Preferably, the raw coal powder and the activator are first stirred and mixed in the kneader at 55-65° C., and then the coal tar and the water are added and stirred and mixed in the kneader to obtain the mixture; Preferably, the molding material is a strip structure; Preferably, the weight ratio of the raw coal powder to the water is (10-15):

1.

8. The method for preparing coal-based activated carbon according to any one of claims 1 to 5, characterized in that: In step S2, the heating rate of the carbonization treatment is 5°C / min to 15°C / min; Preferably, in the step S2, the molding material is dried before the carbonization treatment; More preferably, the drying process is performed by natural air drying; More preferably, in the step S2, the temperature in the furnace is first raised to 250° C. to 300° C. under an inert gas atmosphere, and then the dried molding material is placed in the furnace for the carbonization treatment; Preferably, the carbonization treatment time is 10 min to 30 min.

9. The method for preparing coal-based activated carbon according to any one of claims 1 to 5, characterized in that: In step S3, the heating rate of the activation treatment is 5°C / min to 15°C / min; Preferably, the amount of the activated gas introduced is calculated as the activated gas introduced at a flow rate of 10 ml / min to 30 ml / min per kilogram of the raw coal powder; Preferably, the activation time is 20 min to 100 min.

10. Coal-based activated carbon prepared by the method for preparing coal-based activated carbon according to any one of claims 1 to 9.